Peningkatan Hasil Belajar dengan Metode Pembelajaran Time Token Arends Pada Siswa Sekolah Dasar - Mariyana, Tena; Tame, Tamenia; Wedyawati, Nelly (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
The initial completion of grade IV students at SD Negeri 01 Kenukut is that the learning process is still contextual with learning outcomes not meeting the KKM, 62% of students who do not complete and 37% who complete. The study aimed to determine the increase in learning outcomes with the time token Arends learning model and to find out student responses to the time token Arends learning method. This study uses a quantitative approach in the form of a Quasi-Experimental Design. Data collection techniques using test questions measurement techniques, indirect communication using angles, and documentation techniques using documentation. The tests were analyzed using the t-test. The results showed that there were differences in the learning outcomes of the experimental and control groups. Response questionnaire results obtained an average of 75% (moderate). The conclusion obtained is that the use of the Time Token Arends learning method can improve the learning outcomes of elementary school students and students are happy with the Time Token Arends learning method.